Analisis Ekspor, Impor, dan Jumlah Uang Beredar (M2) Terhadap Nilai Tukar Rupiah - Adhista, Mira (LPPM Universitas Muhammadiyah Mamuju, 2022)
The economy in Indonesia is based on an open economy. In international trade activities, countries are required to compare their currency with the currencies of other countries. The United States currency, namely the dollar, is still used as the standard of world exchange rates and has been used in international transaction activities. The effect of fluctuations in the exchange rate of the rupiah against the dollar is the occurrence of depreciation or appreciation which will affect economic activities in Indonesia. The purpose of this study is to determine the effect of exports, imports, and the money supply (M2), on the rupiah exchange rate in the short and long term. This research is based on data from 1990 to 2018, using the Error Correction Model ECM. The result is a short-term as well as long-term relationship. In the long run, exports and the money supply (M2) significantly affect the exchange rate. Meanwhile, in the short term the money supply (M2) affects the exchange rate.